Comparing Academic and Non-Academic Support Services: Mechanisms Impacting Academic Performance - Yang, Min (International Review of Research in Open and Distributed Learning, 2025)
Learning support services, categorized into academic and non-academic support, have been demonstrated to positively influence student development. However, the distinct mechanisms by which academic and non-academic support services impact academic performance remain underexplored in China. This study seeks to provide comprehensive insights into these mechanisms. A survey was conducted with a sample of 1,234 students to gather data on learning support services, student engagement, and learning performance. Structural equation modeling (SEM) was employed to analyze the conceptual model derived from the survey data. Results revealed that student engagement played a partial mediating role between academic support services and learning performance, while it played a complete mediating role between non-academic support services and learning performance. Furthermore, the analysis of standardized coefficient values reveals that academic support services have a lesser impact on student engagement and learning performance compared to the influence of non-academic support services on these same outcomes. It is suggested that distance education institutions need to pay more attention to non-academic support services and optimize resource allocation to achieve more efficient and rational resource distribution. As numerous traditional face-to-face educational institutions in China expand into online education, they encounter challenges due to isolation between teachers and students. Consequently, the concept of learning support services in distance education has become a significant concern. The findings of this study could provide valuable insights for these institutions.